Circular economy in the agri-food sector: A policy overview - Giulia Chiaraluce (Italian Review of Agricultural Economics (REA), 2021)
Agri-food is the second manufacturing sector in Italy, due to its strategic nature. However,it is affected by several problematics, and one of the most severe is the generation of wastes and by-products. The circular economy could be a winning approach to improve the sustainability of the food supply chain. The objective of this paper is to provide an overview of the current policy situation in Europe, with a focus on Italy. The history of circular economy policies in Europe started recently, and is continuing nowadays with the New Circular Economy Action Plan. Italy is in the top position for circularity, even if it has not yet implemented a proper circular economy policy. Future actions should concentrate on developing innovative circular models for the agri-food sector.
Keywords: L66; O13; Q18; 330; Circular Economy; agri-food sector; sustainability; policy framework; Covid-19; circular business model